2000
DOI: 10.18814/epiiugs/2000/v23i4/005
|View full text |Cite
|
Sign up to set email alerts
|

The garnet placer deposit from SE Spain: industrial recovery and geochemical features

Abstract: The only economic deposit of garnets in Spain is located in the Almería province (SE Spain), forming part of the Neogene Volcanic Complex of El Hoyazo. Due to the high quantity and diversity of the almandine garnets, this area is unique. Garnet occurs as isolated euhedral crystals in the volcanic rock, as the principal component of metapelitic xenoliths in dacite, and as a terrigenous deposit formed by the erosion of the volcanic dome. In this work, we provide new mineralogical and geochemical data, which shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This work presents the first specific study of Th and U bearing minerals which were recently found in the SE Mediterranean margin of Spain (El Hoyazo, Almería province) (Muñoz-Espadas et al 2000). They are REE phosphates which occur as amoeboidal-toelongated inclusions, from around 10 m to 120 µm, hosted in single garnet crystals from dacite lavas and metamorphic rocks ( Figure 1) which form part of a geologically well-defined volcanic outcrop: El Hoyazo Volcanic Complex.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…This work presents the first specific study of Th and U bearing minerals which were recently found in the SE Mediterranean margin of Spain (El Hoyazo, Almería province) (Muñoz-Espadas et al 2000). They are REE phosphates which occur as amoeboidal-toelongated inclusions, from around 10 m to 120 µm, hosted in single garnet crystals from dacite lavas and metamorphic rocks ( Figure 1) which form part of a geologically well-defined volcanic outcrop: El Hoyazo Volcanic Complex.…”
Section: Introductionmentioning
confidence: 84%
“…In addition, El Hoyazo is, following Zeck (1968), where the first described cordierite was found (this mineral occurs in clear association with the garnet). Detailed descriptions of the petrology and geochemistry of the volcanics from the EHC can be found in Zeck (1968Zeck ( , 1970, López Ruiz et al (1977), Molin (1980), Munksgaard (1984Munksgaard ( , 1985, Zeck (1992), Benito (1993), Cesare et al (1997), Benito et al (1999), Lunar et al (1999) and Muñoz-Espadas et al (2000).…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation